Disaster Risk Reduction for Natural Disaster using Mobile Learning Application to Improve the Students Disaster Mitigation Literacy in Elementary School - Wahyudi, Diki; Hidayatullah, Ma’rif (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
One in every hundreds of deaths in Indonesia is caused by natural disasters. Data from the National Disaster Management Agency (BNPB) shows that during 2020 there were 2,925 disaster events in Indonesia which resulted in 370 deaths, 39 missing and 536 injured. Disasters can certainly take many lives and can happen to children or adults. Moreover, children lack knowledge about disaster mitigation. Therefore, it is very important to foster “Disaster Mitigation Literacy” considering that Indonesia is a disaster-prone area. This research aims to design and develop a mobile application that focuses on increasing literacy and reducing the risk of natural disasters. This mobile application developer uses the ADDIE (Analysis, Design, Develop, and Implement) model. In this application contains about handling disasters both before, during and after disasters. This application offers interesting illustrations so that children can easily learn the material with more fun. This application is expected to provide basic information about natural disaster mitigation for elementary school children. The result of the disaster mitigation literacy improvement application shows that this mobile application affects students understanding of natural disaster preparedness and also helps elementary school children to natural disaster issues and solving problems.